Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/diagnostics12061365
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers in Cerebrospinal Fluid of Newly Diagnosed Multiple Sclerosis Patients and Their Link to Iron Deposition and Atrophy

Abstract: Oxidative stress has been implied in cellular injury even in the early phases of multiple sclerosis (MS). In this study, we quantified levels of biomarkers of oxidative stress and antioxidant capacity in cerebrospinal fluid (CSF) in newly diagnosed MS patients and their associations with brain atrophy and iron deposits in the brain tissue. Consecutive treatment-naive adult MS patients (n = 103) underwent brain MRI and CSF sampling. Healthy controls (HC, n = 99) had brain MRI. CSF controls (n = 45) consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The essence of Prx2 is a peroxidase encoded by the Prdx2 gene [ 14 ], which has the effect of decomposing reactive oxygen species (ROS) [ 15 ]. In our earlier study, we determined the protective effect of Prx2 in animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The essence of Prx2 is a peroxidase encoded by the Prdx2 gene [ 14 ], which has the effect of decomposing reactive oxygen species (ROS) [ 15 ]. In our earlier study, we determined the protective effect of Prx2 in animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous cross-sectional study on this cohort, we observed increased CSF levels of PRDX2 that correlated with thalamic atrophy in MS patients. This highlighted the active role of anti-oxidative cytoprotective enzymes in the termination of the inflammatory reaction [ 3 , 32 ]. The lack of association between PRDX2 and other markers of oxidative stress with the degree of volume loss in the longitudinal study may be theoretically related to the positive effect of anti-inflammatory treatment on oxidative stress in MS [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy controls (HC) were recruited from the general community [ 3 , 45 ]. The controls were free of neurologic or other medical disorders affecting the brain and had a normal neurological examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations

Oxidative Stress Markers in Multiple Sclerosis

Jiménez-Jiménez,
Alonso-Navarro,
Salgado-Cámara
et al. 2024
IJMS